Photoelectrochemical sensors based on heterogeneous nanostructures for in vitro diagnostics - Shengli Cao; Ziyu Xie; Gang Xiao; Xinyue Sun; He Diao; Xin Zhou; Zhao Yue (Biosensors and Bioelectronics: X, 2022)
In vitro diagnostics with biochemical sensors are one of the most important technologies for medical diagnosis and the examination of human health. With the improvement of people's living standards, the demand for in vitro diagnostics is increasing, and the requirements for the performance of biochemical sensors are also getting higher. Compared to other biochemical sensors, photoelectrochemical sensors based on heterogeneous nanostructures have excellent light absorption ability and electron transfer performance, and are powerful alternatives for the detection of chemical substances and biochemical molecules for in vitro diagnostics. And this is the main reason why they are a hot topic among relevant analytical methods. However, comprehensive and detailed analyses based on these sensors are rarely reported, especially for in vitro diagnostics, so a complete review of this field is necessary. This review outlines the advantages and disadvantages of various current sensors and further demonstrates the superiority of photoelectrochemical sensors based on heterogeneous nanostructures by comparison. In addition, a detailed classification, introduction of principles and analysis of synthesis methods of heterogeneous nanostructured photoelectrochemical sensors are presented. Based on the above analysis, a detailed description of the use of this type of sensor for in vitro diagnosis of inorganic and organic (micromolecules and macromolecules) molecules in recent years is presented. Predicting and combating relevant diseases are realized by in vitro detection of molecules. Finally, it paves the way for subsequent researchers in the process of realizing practical applications of photoelectrochemical sensing based on heterogeneous nanostructures.